Design and development of an unthethered soft robot - Zhang, Song (Nanyang Technological University, 2023)
Soft robotics is an emerging field that studies the design and implementation of robots made of soft and deformable materials. The main objective of this project is to design, fabricate and test a novel untethered soft robot that can move in different direction and be remotely controlled by a user using a graphical user interface (GUI). The soft robot is made of soft and 3D printed structure changing materials, which actuated by servo motors. The robot is also equipped with a camera system that enables the user to see the surroundings of the robot and guide its movements. The GUI was developed using PyQT5, a Python library for creating cross-platform applications. The GUI allows the user to send commands to the robot via WIFI signal and receive feedback from the camera system. One of the challenges of this project is to find the optimal gaits for the soft robot. To address this challenge, different experiments were conducted using an automated test script that implemented evolution algorithm, which is a bio-inspired optimization technique that mimics the process of natural selection and adaptation. The algorithm generates and evaluates different gaits for the soft robot based on angle of servo motors and time between the motion of two servo motors. The test data were processed and analyzed using Python and Pandas DataFrame, two powerful tools for data manipulation and analysis. The data were also visualized using Plotly, a Python library for creating interactive graphs and charts. Based on the data analysis and graphs, the optimal gaits for different scenarios were identified and applied to the soft robot. Finally, demonstrations of the soft robot’s movement and GUI were conducted to showcase its capabilities and potential applications.